Evaluation of calibrated Kinect gait kinematics using a Vicon motion capture system - Lamine, H.; Bennour, S.; Laribi, M.; Romdhane, L.; Zaghloul, S. (Computer Methods in Biomechanics and Biomedical Engineering, 2017)
Human gait analysis has been widely investigated in several applications: identification of gait impairments, therapy designing for rehabilitation, sports medicine, design of orthoses and prosthetics. Most often, gait analysis requires the use of expensive and complex devices, and as well, the experimental protocol is complicated and demands various steps. In this context, the Microsoft Kinect, a free video gaming controller, could be employed in clinical applications as a low cost and easy-to-use motion capture system.